Standardisation of Fat, Colour and Moisture Levels for Semi-dry Fish Sausages - V.R., Joshi; T.M.R., Setty (Fishery Technology, 2012)
Fermented semi-dry fish sausages were prepared with different levels of fat (5-15%) and colour (0.05-0.25% colour solution). In another experiment sausages prepared with standardised ingredients were subjected to smoking (35-40PC for 2 h) and oven drying (70 or lOO-C for 1 and 2 h) or just oven drying (eOC for l-2h) without smoking. Sausages with 15% fat was faster in fermentation rate, with less growth of lactic acid and other bacteria unlike those of 5 and 10% fat. However, sausages with 10% fat level received, high organoleptic scores. Among the different colour levels, 0.2% was preferred by the panelists. Sausages, smoked and oven dried at 70oC for 1 h. and among non smoked sausages, those dried at 60oC for 2 h were preferred by the panelists.